Instrumen Kebijakan Fiskal dalam Perspektif Ekonomi Islam - Reisa Nadika Markavia; Fidzri Nur Febriani; Fitri Nur Latifah (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2022)
This study aims to determine the fiscal policy at the time of the Prophet and Khulafaurrasydin, the role and objectives of fiscal policy from an Islamic economic perspective, and fiscal policy instruments in Islam. In this research study, a literature review and descriptive approach are used to describe the actual events. So that in writing the article on fiscal policy instruments from the perspective of Islamic economics, it seeks to explain and describe how the role of the state in managing fiscal policy instruments is to be channeled properly and can prosper the people. Sources of data are obtained from scientific journals found on the website database https://scholar.google.co.id. Indexing using keywords. Fiscal policy in Islam itself leads to policies made by the government in referring to the economy in a country into a system of income and expenditure in the form of taxes. Therefore, we need to know what income and expenditure instruments exist in fiscal policy in Islamic economics.